The Effect of Customer Engagement, Customer Experience and Brand Love on Behavioral Intention in E-Commerce Users: The Role of Trust as a Moderation Variable - Fandi Pratama Putra; Ida Bagus Cempena; Achmad Yanu Alif Fianto (Cita konsultindo, 2025)
Advances in digital technology have transformed interactions and transactions in e-commerce. This study analyzes the influence of customer engagement (cognitive, affective, behavioral), customer experience, and brand love on behavioral intention, with trust as a moderating variable. Data from 100 respondents of e-commerce users were analyzed using SEM-PLS. The results showed that all of these factors had a significant positive effect on behavioral intention, except for the insignificant relationship between behavioral customer engagement and brand love. Trust has been shown to moderate the relationship between customer experience and behavioral intention, as well as brand love and behavioral intention, amplifying the positive impact of customer experience and brand love. This research emphasizes the importance of trust in building customer loyalty and provides insights for consumer-focused marketing strategies in the e-commerce industry.